2011
DOI: 10.4269/ajtmh.2011.09-0498
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Safety and Infectivity in Sporozoite Challenge Model of Plasmodium vivax in Malaria-Naive Human Volunteers

Abstract: Abstract. A safe and reproducible Plasmodium vivax infectious challenge method is required to evaluate the efficacy of malaria vaccine candidates. Seventeen healthy Duffy (+) and five Duffy (−) subjects were randomly allocated into three (A-C) groups and were exposed to the bites of 2-4 Anopheles albimanus mosquitoes infected with Plasmodium vivax derived from three donors. Duffy (−) subjects were included as controls for each group. Clinical manifestations of malaria and parasitemia were monitored beginning 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 38 publications
4
50
0
Order By: Relevance
“…22 The second trial was to determine if infection was dependent on the P. vivax strain used for mosquito feeding, using doses of 3 ± 1 mosquitoes shown to be capable of reproducibly infecting humans. 30 All four batches produced infection in virtually all volunteers.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…22 The second trial was to determine if infection was dependent on the P. vivax strain used for mosquito feeding, using doses of 3 ± 1 mosquitoes shown to be capable of reproducibly infecting humans. 30 All four batches produced infection in virtually all volunteers.…”
Section: Resultsmentioning
confidence: 97%
“…22 For the second trial a total of 18 mosquito batches were infected over a similar time period. 30 Eleven batches were discarded because parasite donors presented infectious diseases (Hepatitis, Syphilis, and human T-lymphotrophic virus [HTLV]) ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Herrera et al have demonstrated the robustness and reproducibility of the P. vivax sporozoite challenge model [80,81], which should allow evaluation of efficacy of both pre-erythrocytic and blood stage P. vivax vaccines. A P. vivax blood stage challenge model that establishes experimental blood stage infection in human subjects by transfer of cryopreserved P. vivax patient isolates [82] could also be used to evaluate efficacy of blood stage P. vivax vaccines.…”
Section: Challenges and Directions For P Vivax Vaccine Developmentmentioning
confidence: 99%